The Impact of Risk Management Variables on the Efficiencies of Ghanaian Commercial Banks - Ofosuhene, Joyce (2012)
This dissertation examines the impact of risk on banks efficiency in Ghana. Using the stochastic input distance function, the technical efficiency and change is estimated for all commercial banks of Ghana during the period of 2011-2009. The study uses three different models where in model i there exist only the traditional measures of efficiency (inputs and outputs), in model ii there exist a risk variables named equity and finally model iii introduces another risk variable loan loss provision to find out whether there exist a relationship between pure model of efficiency and the risk-adjusted models. The comparison is made between the models of the distance which integrates the efficiency scores in order to evaluate the performance of the sampled risk variables on the bank’s efficiency. Given the consistency of my results the parametric input distance developed for providing final efficiency estimates and analysis of the impact of these risk variables shows that on average bank efficiency scores had fallen over the period. This is consistent for all the three models considered. The inclusion of loan loss provision as a risk input variable reduced the efficiency of some banks, whilst it significantly improved the efficiency scores of the least performing banks under the pure model. Keywords: Banking Risk (Loan Loss Provision, Equity) Stochastic Input Distance Function, Efficiency Technical Efficiency.